DESIGNING CITY TOURIST ROUTE OF CIREBON, WEST JAVA, INDONESIA - Hidayat Putro, Heru Purboyo (ASEAN Journal on Hospitality and Tourism, 2017)
The existence of a highway or commonly called a toll road, which connects between Cikopo-Palimanan-Kanci-Pejagan, is a factor in the development of tourism in Cirebon. This development is expected to contribute to the increase in the number of tourist visits. Tourists need to be facilitated to obtain good and many experiences while in Cirebon. The conception of tourist routes is used as input for the creation of a framework or direction for government policy for the development of tourism in the medium and long term in the context of developing tourism in Cirebon. The approach used is the concept of 5A which is a key element that must be owned by a destination. 5A consists of Accessibilty, Accommodation, Atraction, Activity, and Amenities. 5 selected tourist attractions are the priorities that are arranged in the Cirebon tourist route.